Análise estrutural de halogenases encontradas em clusters gênicos da biossíntese de antibióticos glicopeptídicos - Cardoso, Tábata Peres [UNESP] (2015)
Various experiments have shown that natural compounds may have their biologic activity altered by presence or absence of halogens. Glycopeptide antibiotics, such as vancomycin and teicoplanin are halogenated natural products and they have substantial importance in the medicine. Halogenases, are enzymes that catalyses the attachment of halogens to a substrate, howerver they are not well understood mainly those ones in glycopeptide biosynthesis. Producing glycopeptides strains were obtained from NRRL collection, they were grown in liquid TSB medium and the DNA was extracted. Three different genes for halogenases [(staI and staK from Streptomyces toyocaensis (compound 47934) and Orf8* from Actinoplanes teichomyceticus (Teicoplanin)] were amplified and cloned into pET28a and pET20a. A synthetic gene for comH from the biosynthesis of complestatin was obtained and also cloned in the pET28a. The expression of these four genes was carried out with the induction by IPTG and the purification was performed by affinity and molecular exclusion. Samples of soluble and insoluble fractions and chromatographic peaks were analyzed on SDS-PAGE gel. Circular Dichroism (CD) and Dynamic Light Scattering (DLS) studies were performed for StaI and ComH. We have also performed molecular modelling for StaI and StaK enzymes because attempts to crystallise all the soluble halogenases did not return any result (only StaI had a single crystal which showed not reproduzible). ComH, StaI and StaK were purified and they had an yellow colour indicating the co-purification with FAD.Orf8* was predominantly insoluble. SDS-PAGE gel showed that StaI had high purity already after the affinity purification and the molecular exclusion indicates that it had a tendency to aggregate. By the analysis of CD was possible to observe the structural integrity of StaI and ComH, which shows, as expected, the presence of -helixes and β-sheets. The DLS analysis shows the oligomerization ...